2015
DOI: 10.1177/1464420715598798
|View full text |Cite
|
Sign up to set email alerts
|

Study on the effects of nano-aluminum-oxide particulates on mechanical and tribological characteristics of chopped carbon fiber reinforced epoxy composites

Abstract: An experimental study has been carried out to investigate the mechanical and tribological characteristics of chopped carbon fiber (CCF) reinforced epoxy composites filled with nano-Al 2 O 3 particulates, as a function of fiber and filler contents. The experiments were conducted using a pin-on-disc wear test apparatus under dry sliding conditions. The coefficient of friction and specific wear rate of these composites was determined as a function of applied normal load, sliding velocity, sliding distance, and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…14 The WS 2 particles lowered the average wear rate of the neat PEEK by 10% and 60% with WS 2 F and WS 2 N, respectively, while the presence of both the carbon-based fillers deteriorated the wear behaviour by 20% (CNT) and as much as three times in the case of the graphene nanopowder. 3 Dass et al 15 investigated the effects of carbon fibre and nano-aluminium oxide particle reinforcements on the mechanical and tribological properties of novel epoxy composites under dry sliding condition.…”
Section: Introductionmentioning
confidence: 99%
“…14 The WS 2 particles lowered the average wear rate of the neat PEEK by 10% and 60% with WS 2 F and WS 2 N, respectively, while the presence of both the carbon-based fillers deteriorated the wear behaviour by 20% (CNT) and as much as three times in the case of the graphene nanopowder. 3 Dass et al 15 investigated the effects of carbon fibre and nano-aluminium oxide particle reinforcements on the mechanical and tribological properties of novel epoxy composites under dry sliding condition.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in the friction coefficient could be attributed to the smoothness in the epoxy composite surface after rubbing for a long distance against the stainless steel disk. Furthermore, Dass et al [10] reported that after rubbing polymeric samples for a long time, the generated heat could melt the surface of the composite. Consequently, a thin film of the melted polymer composite is transmitted to the counterpart.…”
Section: Resultsmentioning
confidence: 99%
“…Epoxy-based thermosetting resin can be used for its chemical and heat resistance [8], high corrosion barrier [9], and it is an electric isolator, in addition to its high stiffness and the simplicity of its production and processing. Such advantages have nominated epoxy for various applications such as helicopter rotors, industrial flooring, pump impellers, and aircraft engines [10]. Nevertheless, epoxy has its drawbacks, such as its brittle nature, which affects its mechanical characteristics and decreases its wear resistance, preventing its utilization in frictional applications [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The same trend was observed in the flexural and compression strength of the specimen, where the values increased from 115–156.56 MPa to 176–204.66 MPa and 48–61.15 MPa to 72–85.65 MPa, respectively. The mechanical properties of the material started to exhibit opposite trends when more nanoparticles were added [ 53 ]. In another published research paper by Mohanty et al (2014), it was discovered that a concentration of 2 wt% alumina nanoparticles was the optimum value to enhance the thermal stability and flexural modulus and strength as well as the impact strength of short carbon fibre-reinforced polymer composites.…”
Section: Methods To Reinforce Recycled Carbon Fibres Propertiesmentioning
confidence: 99%